Avaliação do estabelecimento de mudas de eucalipto sob déficit hídrico - Toledo, João Vitor (2012)
Eucalyptus is a fast growing tree species most used in Brazil, and its cultivation is of the most more advanced, productive and competitive in the world. Stress induces changes and responses in all functional levels the plant organism. The water deficit t